(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Soil samples from different sections of Ajaokuta Steel Complex, Ajaokuta were collected randomly for the analysis of the concentration of selected heavy metals caused by the activities of the iron and steel complex. The results obtained were compared with WHO, NAFDAC and SON standards; and the parameters assessed fall within the permissible limits. The low concentration could be attributed to the fact that the Ajaokuta Steel Company has not been in operation for more than five years. The analysis was done using pH meter and atomic absorption spectrometric technique. The pH of the soil S1 (7.50), S2 (7.60), S3 (7.10) and S5 (7.20) were slightly basic and S4 (6.10) and S6 (6.90) were slightly acidic and the concentration of the heavy metals in ppm were within the permissible range except for Fe which is in a high concentration, which was found to range between 97.4to116.5 mg/Kg. Heavy metal pollutants in the environment are of immense concern globally, so there is need to study and enlighten the habitants of such environments where this giant company is situated as clarified in this study.